Exploring Family Lifestyle: How Families Embrace the Teachings of the Holy Quran in Firoz-Koh City, Afghanistan - Qassem Farhang; Sayed Shir Aqa Hashemi; Obaidullah Agheez (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2023)
The article delves into the family lifestyle through the lens of the Qur'an, employing a descriptive-analytical approach that integrates religious, moral, social, and intellectual dimensions with insights from sociology. It adopts a qualitative approach, employing structured individual interviews and narrative analysis as the primary methods of data collection. The research population comprises the families of Firoz-Koh City, with a sample size of 18 family members selected through random sampling. Information gathered includes the number of children, occupation, and age of marriage. Data analysis is conducted using theoretical coding techniques. The findings reveal the pivotal role of